A new and enantioselective indolizidine synthesis by meso-epoxide alpha-deprotonation-transannular N-C insertion - Hodgson, D; Robinson, L (1999)
Enantioselective α-deprotonation-rearrangement of N-Boc hexahydroazonine oxide 10 using organolithiums in the presence of (-)-sparteine 3 gives the ester 12 in up to 89% ee.